2015
DOI: 10.1097/ajp.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Procedural and Physical Interventions for Vaccine Injections

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 68 publications
2
30
0
4
Order By: Relevance
“…Evidence-based clinical practice guidelines also recommend combining these interventions to reduce vaccination-related needle pain. This includes applying topical anesthetics prior to vaccination; using breastfeeding or sucrose for infants; avoiding the supine position; holding for younger (aged B3 years) and sitting for older children, as well as the rapid injection of intramuscular vaccine without aspiration [86,91,127,128]. The authors recommended various distractions during vaccination, but these recommendations were less supported by the literature.…”
Section: Combination Of Strategiesmentioning
confidence: 92%
See 2 more Smart Citations
“…Evidence-based clinical practice guidelines also recommend combining these interventions to reduce vaccination-related needle pain. This includes applying topical anesthetics prior to vaccination; using breastfeeding or sucrose for infants; avoiding the supine position; holding for younger (aged B3 years) and sitting for older children, as well as the rapid injection of intramuscular vaccine without aspiration [86,91,127,128]. The authors recommended various distractions during vaccination, but these recommendations were less supported by the literature.…”
Section: Combination Of Strategiesmentioning
confidence: 92%
“…Moreover, during vaccination specifically, skin-to-skin contact and holding an infant reduced acute distress [91]. The upright position reduced self-reported fear in children [91]. A systematic review reported that, for older children and adolescents aged 2-19 years, distraction and hypnosis were effective in reducing pain and distress related to needle procedures, including venipuncture, intravenous line insertion, and vaccination [84,92].…”
Section: Non-pharmacological Management Strategiesmentioning
confidence: 97%
See 1 more Smart Citation
“…No research has yet reported effects of low frequency vibration (50-100 Hz) on CRS pain. Most of the published literature has focused on analgesia in the peripheral nervous system [30,31,[57][58][59][60], though some research has reported success treating temporomandibular disorder pain [61,62]. Low frequency vibratory inhibition of nerves associated with the parasympathetic nervous system may be partly responsible for the beneficial effects of treatment [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…27 Although the importance of separating age groups due to the changes in cognitive development has been highlighted in similar reviews, 20 only one review of Psychological interventions excluded studies with participants younger than 3 years old, 17 while several other relevant reviews failed to exclude studies on infants, with data including large proportions of infant reports (23-81%). 19,22,28 With these considerations in mind, we have chosen to review interventions conducted in apparently healthy, school-age children (age 4-15), that do not require training or parent / carer involvement and therefore are appropriate in mass vaccination settings.…”
Section: Introductionmentioning
confidence: 99%